Synthesis and Identification of Aryl and Alkyl Gem‐Dilithium Phosphido‐Boranes: A Boost to the Chemistry of Phosphandiides. Issue 26 (22nd April 2018) - Guang, Jie; Duwald, Romain; Maddaluno, Jacques; Oulyadi, Hassan; Lakhdar, Sami; Gaumont, Annie‐Claude; Harrison‐Marchand, Anne
Abstract: The synthesis and identification of unprecedented gem‐dianionic phosphorus compounds, that is, gem‐dilithium phosphido‐boranes Li2 [RP⋅BH3 ], with R=Ph or Cy, are reported in THF solution. These were obtained by double deprotonation of the corresponding primary phosphine‐borane precursors RPH2 ⋅BH3 . Their in‐depth structural study, based on multinuclear ( 1 H, 6 Li, 7 Li, 11 B, 13 C, 31 P) mono‐ and bi‐dimensional NMR analyses, indicates a strong influence of the phosphorus substituent on the structure of the gem‐dianionic phosphorus structure; a monomeric arrangement was obtained when R=phenyl, whereas a cyclic oligomer was observed for R=cyclohexyl. These compounds represent a new type of useful reagent, and their access paves the way for the concept of "RP synthons" (i.e., RP 2− phosphandiides), likely to be the most flexible precursors of a variety of phosphorus targets. Abstract : Aryl and alkyl phosphandiides, stabilized by complexation with a borane group, were synthesized and their structure in THF solution is reported. A monomer is identified for the gem‐dilithium phosphido‐boranes Li2 [PhP⋅BH3 ], whereas Li2 [CyP⋅BH3 ] arranges as a cyclic oligomer. This study highlights a new type of useful reagent and opens the door to the concept of "RP synthons" (RP 2− phosphandiides), likely to be the most flexible precursors of a multitude of tertiary phosphines.